The seven practices of mentally effective athletes a brief guide to harnessing skills from sport psychology - Wald, Raphi PsyD, ABN, CMPC (London New York Routledge, Taylor & Francis Group, 2019)
Once athletes reach the highest levels of competition in college and professional sports, the mental aspect of the game becomes increasingly vital to performance. The Seven Practices of Mentally Superior Athletes is a short and snappy reference text intended for repeated use that explains the importance of the mental side of the game and offers concise advice for improvement. Wald outlines the most important sport psychology skills in a way that can be easily understood and applied to athletes regardless of what sport they play. It also features illustrative stories that demonstrate exactly how these skills can be applied on the field, court, course, or arena. this book is particularly helpful to busy athletes with demanding lifestyles. it will also be useful for coaches who want to continue their education and learn more about sport psychology and how to implement these mental training habits with their athletes
Deal with underlying psychological problems (mental health) -- A penny saved (maintain mental energy) -- Own your thoughts (focus) -- Curb your enthusiasm (pre-performance routines and focus) -- Stand tall (confidence) -- Go beyond mental toughness (mental endurance) -- Be flexible (openness to change)
Includes index
Keywords: Mental health -- Handbooks, manuals, etc; Athletes -- Psychology -- Handbooks, manuals, etc; Sports -- Psychological aspects -- Handbooks, manuals, etc